Business model innovation in the aviation industry. (1st January 2013) - Schneider, Sabrina; Spieth, Patrick; Clauss, Thomas
In response to changing sources of value creation, business model innovation has recently emerged as a concept that allows dealing with volatile environments. Focusing on the aviation industry, we aim at enhancing the understanding of drivers, elements and forms of business model innovation. We use an inductive, theory-building design that allows patterns of business model innovation to come to light across multiple case studies of Maintenance, Repair and Overhaul (MRO) companies in the aviation industry. In line with prior theory, we find that a range of supply and demand-driven effects trigger the need for business model innovation in the aviation sector. We identify aircraft manufacturer market characteristics and structural airline industry characteristics as drivers of MRO business model innovation. New MRO value offerings and MRO value creation were set as constituting elements of innovating MRO business models resulting in customer benefit-oriented and value co-creation-oriented business model innovation.